Environmental impacts of latent heat thermal energy storage systems - da Silva Santos, Humberto; Lázaro Fernández, Ana; Guillen Lambea, Silvia (Jornada de Jóvenes Investigadores del I3A, 2025)
Latent thermal energy storage integrated into energy systems can be a solution to the intermittency of renewable energies. The objective of this work is to investigate how operational parameters and phase change material properties influence the environmental impacts of thermal energy storage systems through a proposed mathematical correlation, thereby enabling informed decisions in the thermal energy storage sector.